PENGARUH DIMENSI KUALITAS PELAYANAN TERHADAP KEPUASAN MASYARAKAT PADA PROSES PEMBUATAN SIM DI SATLANTAS SATUAN PENYELENGGARA ADMINISTRASI SIM (SATPAS) POLRES KENDARI - Muhammad Aris; Murdjani Kamaluddin; Muhammad Masri (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2020)
The purpose of this study was to determine the effect; 1) Simultaneously the dimensions of service quality consisting of tangibles, reliability, responsiveness, assurance, on community satisfaction. 2) partially the tangible dimension to community satisfaction. 3) partially the dimension of reliability to community satisfaction. 4) partially the dimensions of responsiveness to community satisfaction. 5) partially the dimension of assurance to community satisfaction. 6) partially the dimension of empathy to community satisfaction. The research design used is quantitative research. The data used are secondary and primary data. Data analysis usingSPSS software version 20. The sampling technique uses accidental sampling totaled 48 applicants who made SIM at the Kendari Police SATPAS. The results showed that; 1) The dimensions of service quality simultaneously have a positive and significant effect on community satisfaction. 2) The dimension of physical evidence (tangible) partially has a positive and significant effect on community satisfaction. 3) The dimension of reliability partially has a positive and significant effect on community satisfaction. 4) The dimension of responsiveness (responsiveness) partially has a positive and significant effect on community satisfaction. 5) The partially assurance dimension has a positive and significant effect on community satisfaction. 6) Dimensions of empathy (empathy) partially have a positive and significant effect on community satisfaction.